(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Occasionally the SASHT Executive requests that the SASHT constitution is displayed in a Yesterday&Today edition to inform and/or update their members. Members are invited to request a review of any section of the SASHT constitution at an SASHT General Meeting. Prior consent of a section review must be received in written form by the Secretariat of the SASHT or the Chairperson/vice Chairperson of the SASHT (see communication details in the SASHT AGM-minute).